Antecedents of science anxiety in elementary school. Issue 3 (7th May 2021) - Henschel, Sofie
Abstract: Based on the control-value theory of achievement emotions, the study examines elementary school students' science performance and control-value beliefs (self-concept, intrinsic and achievement value) as antecedents of their cognitive (worry) and affective (nervousness) science anxiety. Performance in the science topic "floating and sinking" was assessed and self-reported data on control-value beliefs and worry and nervousness about science were collected from 370 students at three time points during third grade. Results from structural equation modeling support the control-value theory and show that self-concept completely mediated the negative effect of prior science performance on both anxiety components. By contrast, value beliefs did not function as mediators and only achievement value positively predicted nervousness and worry, whereas no effect of intrinsic value was observed. Results are invariant across gender and indicate stereotypical mean differences in science anxiety components that were not due to differences in the predictor variables.